Comparison of Mycobacterium ulcerans (Buruli ulcer) and Leptospira sp. (Leptospirosis) dynamics in urban and rural settings. - Marine Combe; Rodolphe Elie Gozlan; Soushieta Jagadesh; Camilla Jensen Velvin; Rolland Ruffine; Magalie Pierre Demar; Pierre Couppié; Felix Djossou; Mathieu Nacher; Loïc Epelboin (Public Library of Science (PLoS), 2019)
Background Zoonotic pathogens respond to changes in host range and/or pathogen, vector and host ecology. Environmental changes (biodiversity, habitat changes, variability in climate), even at a local level, lead to variability in environmental pathogen dynamics and can facilitate their transmission from natural reservoirs to new susceptible hosts. Whilst the environmental dynamics of aquatic bacteria are directly linked to seasonal changes of their habitat they also rely on the ecological processes underpining their transmission. However data allowing the comparison of these ecological processes are lacking. Here we compared the environmental dynamics of generalist and vector-borne aquatic bacterial pathogens in the same unit of time and space, and across rural and urban habitats in French Guiana (South America). Principal findings Using Leptospira sp. and Mycobacterium ulcerans we performed an environmental survey that allowed the detection of both pathogens in urban vs. rural areas, and during rainy vs. dry weather conditions. All samples were subjected to qPCR amplifications of LipL32 (Leptospira sp.) and IS2404 and KR (M. ulcerans) genetic markers. We found (i) a greater presence of M. ulcerans in rural areas compared with Leptospira sp., (ii) that modified urban environments were more favourable to the establishment of both pathogens, (iii) that Leptospira sp. presence was enhanced during the rainy season and M. ulcerans during the dry period, and (iv) differences in the spatial distribution of both bacteria across urban sites, probably due to the mode of dissemination of each pathogen in the environment. Conclusions We propose that in French Guiana simplified and modified urban ecosystems might favour leptospirosis and Buruli ulcer emergence and transmission. Moreover, disease risk was also constrained by seasonality. We suggest that the prevention of aquatic bacterial disease emergence in impoverished urban areas of developing countries would benefit from seasonal diseases targeted surveys, which would maximise limited budgets from cash-strapped health agencies.